The Using of Spelling Bee Games in Improving The Students ' Reading Skill (Karya Ilmiah Mahasiswa (KIMA), 2026)
Nur Hunaisya. 2024. The Using of Spelling Bee Games in Improving the Students' Reading Skill. (Supervised by Muhajir and Rizkariani Sulaiman)This research aims is to investigate the using of Spelling bee games in improving the students' reading skills. The research employs a qualitative approach. Findings indicate a positive contribution of the Spelling Bee game to the enhancement of ninth-grade students' reading skills. Results from interviews and questionnaires reveal a consensus among students regarding the benefits of the game. The research sample consists of 31 students from grade IX-7 at SMP Negeri 23 Makassar. The study underscores the importance of integrating interactive educational activities for the development of students' reading skills. In conclusion, the Spelling Bee game emerges as a valuable tool for improving students' reading proficiency and fostering a dynamic and meaningful learning environment.